posted by Kim .
I'm haivng troulbe proving the deriviation of this formula on my own...
could you please help me derive the proof of the formula or maybe show me one thansk...
I need to prove this formula
period of a mass spring system in simple harmonic motion
T = 2 pi square root of (m/k)
period = 2 pi X square root of (mass divided by spring constant)
F = m a
F = -k x for spring of constant k in N/m
m a = - k x
now assume motion of form x = A sin (2 pi f t)
dx/dt = velocity = A (2 pi f) cos 2 pi f t)
d velocity/dt = a = -A (2 pi f)^2 sin (2 pi f t)
or in other words
a = - x (2 pi f)^2
- k x = m [ - x (2 pi f)^2 ]
(2 pi f)^2 = k/m
2 pi f = sqrt (k/m)
but T = 1/f
T = 2 pi sqrt (m/k)